Do scaling agile frameworks address global software development risks? An empirical study - Beecham, Sarah; Clear, Tony; Lal, Ramesh; Noll, John (The Journal of systems and software, 2021)
Driven by the need to coordinate activities of multiple agile development teams cooperating to produce a large software product, software-intensive organizations are turning to scaling agile software development frameworks. Despite the growing adoption of various scaling agile frameworks, there is little empirical evidence of how effective their practices are in mitigating risk, especially in global software development (GSD), where project failure is a known problem. In this study, we develop a GSD Risk Catalog of 63 risks to assess the degree to which two scaling agile frameworks–Disciplined Agile Delivery (DAD) and the Scaled Agile Framework (SAFe)–address software project risks in GSD. We examined data from two longitudinal case studies implementing each framework to identify the extent to which the framework practices address GSD risks. Scaling agile frameworks appear to help companies eliminate or mitigate many traditional risks in GSD, especially relating to users and customers. However, several important risks were not eliminated or mitigated. These persistent risks in the main belonged to the Environment quadrant highlighting the inherent risk in developing software across geographic boundaries. Perhaps these frameworks (and arguably any framework), would have difficulty alleviating, issues that appear to be outside the immediate control of the organization. •63 risks in our GSD Risk Catalog support decision makers and reduce uncertainty.•Risks arise both when teams are distributed, and individuals work from home.•Both DAD and SAFe theoretically address almost all risks in this expanded catalog.•Empirical evidence suggests SAFe and DAD eliminate nearly half of GSD risks.•Some GSD risks cannot be eliminated, but their impact can be mitigated.